2021
DOI: 10.1002/brb3.2171
|View full text |Cite
|
Sign up to set email alerts
|

Is obsessive–compulsive personality disorder related to stress‐related exhaustion?

Abstract: Stress-related diagnoses have since 2010 been the fastestgrowing cause of sick leave in Sweden according to the Swedish Social Insurance Agency (Försäkringskassan, 2017b). In 2016, psychiatric diagnosis, especially reaction to severe stress and adjustment disorders (F43) (World Health Organization, 1992), was the most common cause (44%) for long-term sick leave in Sweden (Försäkringskassan, 2017a(Försäkringskassan, , 2017b. A recent review of burnout in workplaces indicates that increased sick leave due to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(45 reference statements)
0
5
0
Order By: Relevance
“… 22 Those who had not recovered from exhaustion disorder reported higher incidence of obsessive–compulsive personality disorder compared with those who had recovered. 29 Two studies report that quantitative work demands were the most prevalent stressors for individuals with exhaustion disorder, 26 , 30 followed by private relational conflicts. 30 In a prospective medical chart study, Skoglund et al 33 investigated whether antidepressant medication was associated with sick leave during a 12-month period but found no such association.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Those who had not recovered from exhaustion disorder reported higher incidence of obsessive–compulsive personality disorder compared with those who had recovered. 29 Two studies report that quantitative work demands were the most prevalent stressors for individuals with exhaustion disorder, 26 , 30 followed by private relational conflicts. 30 In a prospective medical chart study, Skoglund et al 33 investigated whether antidepressant medication was associated with sick leave during a 12-month period but found no such association.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 studies included in this category, seven were cross-sectional and described self-rated symptoms and experiences. 22,[26][27][28][29]31,32 Four longitudinal cohort studies explored within-group symptom progression over time, [23][24][25]33 of which one was based on medical chart data. 33 Another two studies investigated symptoms 21 and stressors 30 as reported in medical charts for individuals diagnosed with exhaustion disorder.…”
Section: Symptoms Course and Contextmentioning
confidence: 99%
“…Several other factors could also be related to long-term exhaustion and should be explored, one being personality traits. Thus, a recent study from our research group found that obsessive-compulsive personality disorder (OCPD), assessed by a self-reported screening questionnaire, was significantly more common among patients with ED who had not recovered 7-10 years after diagnosis compared to former ED patients that had recovered [34]. Taken together, it is plausible that, for some individuals, both personality traits and external stressors contribute to the long-term exhaustion to different degrees.…”
Section: Discussionmentioning
confidence: 96%
“…Another aspect connected to the first theme “it’s about who I am” is the struggle described by the patients regarding the perfectionism ( Frost et al, 1990 ; Noordik et al, 2011 ; Bovornusvakool et al, 2012 ; Hill and Curran, 2016 ; Gulin et al, 2021 ). One negative consequence of perfectionism and overperformance is the influence it can have on the recovery process.…”
Section: Discussionmentioning
confidence: 99%